The incidence of emergence delirium and risk factors following sevoflurane use in pediatric patients for day case surgery, Kingston, Jamaica - Gooden,Rachel (2014)
Background and objectives: Emergence delirium is a distressing complication of the use of sevoflurane for general anesthesia. This study sought to determine the incidence of emergence delirium and risk factors in patients at a specialist pediatric hospital in Kingston, Jamaica. Methods: This was a cross-sectional, observational study including pediatric patients aged 3-10 years, ASA I and II, undergoing general anesthesia with sevoflurane for elective day-case procedures. Data collected included patients' level of anxiety pre-operatively using the modified Yale Preoperative Anxiety Scale, surgery performed, anesthetic duration and analgesics administered. Postoperatively, patients were assessed for emergence delirium, defined as agitation with non-purposeful movement, restlessness or thrashing; inconsolability and unresponsiveness to nursing and/or parental presence. The need for pharmacological treatment and post-operative complications related to emergence delirium episodes were also noted. Results: One hundred and forty-five (145) children were included, with emergence delirium occurring in 28 (19.3%). Emergence delirium episodes had a mean duration of 6.9±7.8 min, required pharmacologic intervention in 19 (67.8%) children and were associated with a prolonged recovery time (49.4±11.9 versus 29.7± 10.8 min for non-agitated children; p<0.001). Factors positively associated with emergence delirium included younger age (p = 0.01, OR 3.3, 95% CI 1.2-8.6) and moderate and severe anxiety prior to induction (p <0.001, OR 5.6, 95% CI 2.3-13.0). Complications of emergence delirium included intravenous line removal (n = 1), and surgical site bleeding (n = 3). Conclusion: Children of younger age with greater preoperative anxiety are at increased risk of developing emergence delirium following general anesthesia with sevoflurane. The overall incidence of emergence delirium was 19%.